Development thought, policy advise [sic] and economic development in Africa in the 20th century : lessons for the 21st century - Garba, Abdul-Ganiyu.; Nigerian Economic Society (Ibadan : Published for the Nigerian Economic Society by Ibadan University Press, 2003)
The book is a contribution of many scholars in the field of economics and social sciences. It is divided into Four (4) different parts. Part one (1) deals with Evolution of development thought and problems of development. Part (2) is on the review of development research, policy support and dissemination activities of Nigerian and African societies and institutions. While part three (3) discusses development lending and patterns of development. Lastly, part four (4) considers lessons for the 21st Century.
Includes bibliographical references and index.
usc 07/06/17
Loans
Keywords: Africa; Africa